Adaptations in the kidney of Palm Civet, Paradoxurus hermaphroditus (Schrater) - Patil Kishor G; Janbandhu Kishor S; Shende Virendra A; Ramteke Asha V; Patil Megha K (International Journal of Life Sciences, 2016)
The kidneys of Paradoxurus hermaphroditus hermaphroditus were simple, typically bean shaped, possessing single papillary cone in the central region surrounded by thick medullary tissues. The medulla further differentiated into outer and inner regions; which was distinguished by the varying diameter and orientation of the uriniferous tubule. The outer thin cortex mainly consists of Bowman’s capsules enclosing the glomerulus and surrounded by the dense convolutions of proximal and distal tubules which were distinguished by vary in luminal diameter and the presence of microvillar brush border in the proximal tubules; the medulla is further differentiated histologically into outer and inner zones. From the outer medullary zone the large number of long medullary rays invades deep into the cortical region; sometimes up to the outer border of the kidney. The thick medulla and long medullary rays represents the long loop of Henle adapted for maximum water reabsorption and urine consentration. The distinct dense network of branches of renal vessels and the capillaries on the outer surface of kidneys indicate the rich supply to the Bowman’s capsule and increased filtration rate.